2014
DOI: 10.1002/poc.3309
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and solvatochromic behavior of branched oligophenylenes with hydroxy groups

Abstract: Investigation of the solvatochromic behavior in branched oligophenylenes (OPs) will lead to a better understanding of intramolecular charge transfer behavior in the aromatic compounds and toward the development of new functional materials. However, there is no report on solvatochromism of branched OP. In this study, branched OPs with phenolic hydroxy groups were synthesized by using reactions with transition metal complexes. The treatment of these compounds with a base produced corresponding deprotonated speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…1,3,5-Tris(4-hydroxyphenyl)benzene (THPB) and [1,1′:4′,1″:4″,1‴-quaterphenyl]-4,4‴-diol (DHQP) were synthesized by applying methods reported previously. 38,39 ■ ASSOCIATED CONTENT * S Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%
“…1,3,5-Tris(4-hydroxyphenyl)benzene (THPB) and [1,1′:4′,1″:4″,1‴-quaterphenyl]-4,4‴-diol (DHQP) were synthesized by applying methods reported previously. 38,39 ■ ASSOCIATED CONTENT * S Supporting Information…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This shift seems to be ascribed to the charge transfer from the N – anions generated via the deprotonation of the imidazole rings to the oligomer backbone. It has been reported that the deprotonation of OH group(s) of the aromatic compounds by NaH causes charge transfer from the O – anion to the inner aromatic rings, accompanied by a bathochromic shift of λ max . …”
Section: Resultsmentioning
confidence: 99%